Modification of activity and specificity of haloalkane dehalogenase from Sphingomonas paucimobilis UT26 by engineering of its entrance tunnel - Chaloupková, Radka; Sýkorová, Jana; Prokop, Zbynek; Jesenská, Andrea; Monincová, Marta; Pavlová, Martina; Tsuda, Masataka; Nagata, Yuji; Damborský, Jirí (The Journal of biological chemistry, 2003)
Structural comparison of three different haloalkane dehalogenases suggested that substrate specificity of these bacterial enzymes could be significantly influenced by the size and shape of their entrance tunnels. The surface residue leucine 177 positioned at the tunnel opening of the haloalkane dehalogenase from Sphingomonas paucimobilis UT26 was selected for modification based on structural and phylogenetic analysis; the residue partially blocks the entrance tunnel, and it is the most variable pocket residue in haloalkane dehalogenase-like proteins with nine substitutions in 14 proteins. Mutant genes coding for proteins carrying all possible substitutions in position 177 were constructed by site-directed mutagenesis and heterologously expressed in Escherichia coli. In total, 15 active protein variants were obtained, suggesting a relatively high tolerance of the site for the introduction of mutations. Purified protein variants were kinetically characterized by determination of specific activities with 12 halogenated substrates and steady-state kinetic parameters with two substrates. The effect of mutation on the enzyme activities varied dramatically with the structure of the substrates, suggesting that extrapolation of one substrate to another may be misleading and that a systematic characterization of the protein variants with a number of substrates is essential. Multivariate analysis of activity data revealed that catalytic activity of mutant enzymes generally increased with the introduction of small and nonpolar amino acid in position 177. This result is consistent with the phylogenetic analysis showing that glycine and alanine are the most commonly occurring amino acids in this position among haloalkane dehalogenases. The study demonstrates the advantages of using rational engineering to develop enzymes with modified catalytic properties and substrate specificities. The strategy of using site-directed mutagenesis to modify a specific entrance tunnel residue identified by structural and phylogenetic analyses, rather than combinatorial screening, generated a high percentage of viable mutants.
Keywords: hydrolasy; Models, Molecular; substrátová specifita; Sphingomonas; Protein Folding; leucin; Mutation; mutageneze cílená; glycin; katalýza; kinetika; aminokyseliny; Catalysis; Alanine; Kinetics; Mutagenesis, Site-Directed; Amino Acids; Glycine; cirkulární dichroismus; vazebná místa; Substrate Specificity; Catalytic Domain; katalytická doména; sbalování proteinů; fylogeneze; alanin; multivariační analýza; Hydrolases; Binding Sites; Leucine; mutace; molekulární modely; Multivariate Analysis; Phylogeny; Circular Dichroism; Escherichia coli